2018
DOI: 10.1111/jasp.12498
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of achievement goals and task complexity on enjoyment, mental focus, and effort

Abstract: Several empirical studies have suggested that achievement goal researchers should put a greater emphasis on identifying factors that may moderate the effects of achievement goals on motivation and related outcomes. In line with this recommendation, the current study sought to examine how one task characteristics (task complexity) may moderate the impact of achievement goals on the motivational outcomes of task enjoyment, mental focus, and exerted effort. Consistent with both the theoretical foundations of achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The research on cognitive effort seems to regard an emotional (i.e., intrinsic) reward, such as boosting self-esteem or feeling good about oneself, somewhat lightly as compared to biological (e.g., foods), cognitive (e.g., a correct answer), social (e.g., approval), and other types (e.g., monetary) of reward ( Donovan, Hafsteinsson, & Lorenzet, 2018 ; Lallement et al, 2014 ; Kurzban, Duckworth, Kable, & Myers, 2013 ; Milyavskaya, Inzlicht, Johnson, & Larson, 2018 ; Schouppe, Demanet, Boehler, Ridderinkhof, & Notebaert, 2014 ). In addition, cognitive effort is generally regarded as a manifestation of human executive function or general intelligence, so it has often been measured in the context of productive or improved performance ( Kurzban et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The research on cognitive effort seems to regard an emotional (i.e., intrinsic) reward, such as boosting self-esteem or feeling good about oneself, somewhat lightly as compared to biological (e.g., foods), cognitive (e.g., a correct answer), social (e.g., approval), and other types (e.g., monetary) of reward ( Donovan, Hafsteinsson, & Lorenzet, 2018 ; Lallement et al, 2014 ; Kurzban, Duckworth, Kable, & Myers, 2013 ; Milyavskaya, Inzlicht, Johnson, & Larson, 2018 ; Schouppe, Demanet, Boehler, Ridderinkhof, & Notebaert, 2014 ). In addition, cognitive effort is generally regarded as a manifestation of human executive function or general intelligence, so it has often been measured in the context of productive or improved performance ( Kurzban et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Song et al (2015) observed that adolescents who receive positive messages from social agents are likely to adopt mastery goals, which are associated with positive emotional responses. Donovan et al (2018) also reported that children with mastery goals tend to have greater task engagement since they focus on knowledge acquisition and the learning process. In a meta-analysis, Huang (2011) summarized the relationship between achievement goals and achievement emotions such as enjoyment and interest.…”
Section: The Mediation Of Mastery Goal Orientation and Reading Enjoymentmentioning
confidence: 97%
“…In other words, mastery goals might serve as a mediator between social support and achievement. Students who have mastery goals are also considered intrinsically motivated and have high task enjoyment ( Donovan et al, 2018 ). Such motivational processes have been positively associated with achievement outcomes in many domains (e.g., Huang, 2011 ; Putwain et al, 2018 ; Eccles and Wigfield, 2020 ), though less consistent findings have been observed for students’ reading outcomes ( Wolters et al, 2017 ).…”
Section: Mastery Goal Orientation Reading Enjoyment and Reading Proficiencymentioning
confidence: 99%
“…Therefore, they often perceive the task requirements as being difficult, which could be negatively related to their job performance. Donovan et al (2018) demonstrated that employees' perceived technology complexity determined their job performance. Although the perceived complexity of technology varies subjectively, its negative impact on employee performance has been supported in various contexts (Siawsh et al, 2019).…”
Section: Hypothesis Development Crowdsourced Food Delivery Workers' L...mentioning
confidence: 99%